A rare case of recurrent medial dislocation of the 1st metatarsophalangeal joint in a professional athlete. (June 2021) - Shah, Rajiv; DeNiese, Pascal; Bhatia, Deepak
Highlights: Dislocations of the first metatarsophalangealjoint are rare, and recurrent dislocations unique. Kabbadi is a contact sport with played occasionally without footwear. Treatment for recurent medial dislocations are not described. Palmaris longus graft was used to reconstruct the lateral capuloligamentous structures. Abstract: Dislocations of the first metatarsophalangealjoint are rare, and recurrent dislocations unique. A national-level Kabaddi player dislocated his right first metatarsophalangeal joint while playing a game bear footed. After self-manipulative reduction, the patient had multiple dislocations. The patient reported after a year of injury with complaints of recurrent medial dislocations of the first metatarsophalangeal joint. At surgery, reconstruction of deficient lateral capsule-ligamentous structures of the first metatarsophalangeal joint was done with Palmaris longus autograft. The patient returned to sports in six months and was followed up for more than two years. The case is unique in the form that recurrent medial dislocation of first metatarsophalangeal dislocation is not described. Level of clinical evidence: Level V.